THE IMPACT OF FINANCIAL LEVERAGE ON EARNINGS PER SHARE IN THE INDONESIAN BANKING SECTOR - Erik Nugraha; Febi Wulandari; R. Aryanti Ratnawati (PT. Altin Riset Publishing, 2026)
Earning Per Share (EPS) is a ratio used to measure the net income earned by a company relative to the number of outstanding shares, serving as a key indicator for investors in assessing a company’s profitability and potential returns. However, an increase in Financial Leverage does not necessarily lead to a higher EPS. This study aims to examine and analyze the effect of Financial Leverage, measured by the Debt to Asset Ratio (DAR) and Debt to Equity Ratio (DER), on Earning Per Share (EPS) in banking sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The research method employed is a quantitative approach using panel data regression analysis. The research data were obtained from the annual financial statements of 22 companies selected through purposive sampling. The results indicate that Financial Leverage measured by the Debt to Asset Ratio (DAR) has a significant effect on Earning Per Share (EPS), while Financial Leverage measured by the Debt to Equity Ratio (DER) has a negative and significant effect on Earning Per Share (EPS). However, simultaneously, Financial Leverage does not have a significant effect on Earning Per Share (EPS).